2022
DOI: 10.3390/genes13050870
|View full text |Cite
|
Sign up to set email alerts
|

Transmission Distortion of MCT1 rs1049434 among Polish Elite Athletes

Abstract: Background: To date, nearly 300 genetic markers were linked to endurance and power/strength traits. The current study aimed to compare genotype distributions and allele frequencies of the common polymorphisms: MCT1 rs1049434, NRF2 rs12594956, MYBPC3 rs1052373 and HFE rs1799945 in Polish elite athletes versus nonathletes. Methods: The study involved 101 male elite Polish athletes and 41 healthy individuals from the Polish population as a control group. SNP data were extracted from whole-genome sequencing (WGS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…All WGS data analyses were performed with Hail (v. 0.2.85) [ 29 ]. WGS and quality control (QC) was performed as described previously [ 30 ]. For this study, after QC whole-genome .vcf files were filtered to contain variants only in MSTN (40 variants), ACVR2A (200 variants), and ACVR2B (152 variants).…”
Section: Methodsmentioning
confidence: 99%
“…All WGS data analyses were performed with Hail (v. 0.2.85) [ 29 ]. WGS and quality control (QC) was performed as described previously [ 30 ]. For this study, after QC whole-genome .vcf files were filtered to contain variants only in MSTN (40 variants), ACVR2A (200 variants), and ACVR2B (152 variants).…”
Section: Methodsmentioning
confidence: 99%
“…From 7 articles that met the inclusion criteria related to MCT1 gene polymorphism, 1392 endurance athletes and 3834 controls have been included in the study (Ben Zaken et al 2015 ; Dzitkowska-Zabielska et al 2022 ; Fedotovskaya et al 2014 ; Guilherme et al 2021 ; Piscina-Viúdez et al 2021 ; Saito et al 2021 ; Sawczuk et al 2015 ). When analyzing the MCT1 (rs1049434) SNP genotypes, the overall analysis showed that endurance athletes [OR: 0.17 [0.02; 0.32]] and Caucasian athletes in the subgroup [OR: 0.42 [0.26; 0.58]] had a higher frequency of the T/T genotype ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The MCT1 gene (monocarboxylate transporter 1), also known as SLC16A1, is a member of metabolic genes (Dzitkowska-Zabielska et al 2022 ). The MCT1 gene encodes a cotransport that carries blood lactate to type I muscle fibers in oxidative muscle fibers (Saito et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%